PROBIOTIC-BASED POND MANAGEMENT STRATEGY TO IMPROVE THE CULTURE PERFORMANCE OF PACIFIC WHITE SHRIMP Litopenaeus vannamei - Andri Iskandar; Virda Ratna Yuniar; Wiyoto Wiyoto; Dian Eka Ramadhani; Muhammad Ahya Rafiuddin; Wida Lesmanawati (Universitas Mataram, 2026)
Pacific white shrimp Litopenaeus vannamei aquaculture has become a primary alternative to increase national aquaculture production following the decline in tiger shrimp farming due to disease outbreaks. However, the grow-out phase still faces challenges such as limited availability of high-quality post-larvae and deteriorating environmental conditions. The application of probiotics is considered a promising approach, as it can improve water quality, suppress pathogens, and enhance shrimp growth and resilience. This study integrates probiotic application into the grow-out management system to improve production efficiency and sustainability. The research was conducted through direct observation and active participation in farming activities, combined with secondary data collection from verified sources. Observed parameters included mean body weight (MBW), average daily growth (ADG), and survival rate (SR). The grow-out activities involved pond preparation, stocking of post-larvae at a density of 120–180 individuals/m² following acclimatization, blind feeding during the first 10 days, and feed administration based on the feeding rate (FR) thereafter. Daily water quality management and disease control were also carried out. The cultivation period lasted for three months, followed by partial and total harvesting, yielding up to 3 tons of shrimp per pond. Post-harvest, the shrimp were sorted and distributed to consumers using refrigerated vehicles.